Arranjo produtivo local: o caso de São João Del Rei-MG - Silveira, Ana Carla Prado da (2008)
The purpose of this dissertation was to investigate the process of Local Productive Arrangement (LPA) of tin in Sao Joao del-Rei – A7 Estanho, focusing their contributions to the local development of this municipality. The work was conducted by a theoretical discussion on the situation of micro and small companies in Brazil, on the economic and social importance of local productive arrangements, its impact on regional and/or local development, mainly municipalities without infrastructure to attract large businesses, and on public policies that are in progress and is back to the promotion of such cluster. Fourteen interviews were conducted in the city of Sao Joao del-Rei: six members of the association, an officer, two representatives of the main partner institutions, a representative of the local government and four members of the civil society who had relevant information on the A7. The method employed in the processing of the data was the analysis of content. As results, regarding the analysis of the programs that have resulted and / or support the cluster, it was found that two programs were more striking in their contributions to the association: the Empreender Program, launched by Federaminas, which enabled the union of entrepreneurs in around a common goal, and the Via Design Project, launched by Sebrae, which has a number of advantages to the group, consolidating it on the market. Regarding the participation of the various actors (members of the A7, public power, institutions, civil society) in the construction of LPA, you can see that the level of expertise and commitment varied according to the personal motivations, positions or functions exercised and level of formal relationship with the association. The contributions to municipality local development, generated by the productive arrangement, were listed as generating jobs and income, yet so nascent, but with possibilities for future growth and dissemination of São João del-Rei`s tourism and culture.